IN SILICO STUDY OF APIGENIN AND ITS DERIVATIVES AS POTENTIAL INHIBITORS OF TNF-Α AND MMP-9 FOR BURN WOUND HEALING - Baharun, Rasyid; Rini Madyastuti, Purwono; Bayu Febram, Prasetyo; Vetnizah, Juniantito (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
The prevalence of burns ranks fourth in trauma after traffic accidents, falls, and violence. The prevalence of burns ranks fourth in trauma after traffic accidents, falls, and violence. The healing of burn wounds results from a complex inflammatory response where pro-inflammatory cytokines, for instance, TNF-α and MMP-9, play a pivotal role. Flavonoids with strong anti-inflammatory activity are apigenin, this compound comes from plants. In this study, we evaluated apigenin and its derivatives to determine their effectiveness as burn wound healing agents using molecular docking modeling techniques. To evaluate the molecular docking of these compounds with their target proteins, we used computer-aided drug design tools such as AutoDock Vina, PyMOL, and Discovery Studio. The data showed that apigenin compounds have better affinity than natural ligands to inhibit MMP-9 which can increase the rate of the inflammatory phase of burn wound healing. These findings indicate that apigenin and its derivatives have good potential to be candidates in the development of new therapeutic interventions for burn wound healing.